High-Throughput Sequencing Reveals Tobacco and Tomato Ringspot Viruses in Pawpaw - Jiyeong Choi; Anya Clara Osatuke; Griffin Erich; Kristian Stevens; Min Sook Hwang; Maher Al Rwahnih; Marc Fuchs (Plants, 2022)
Pawpaw (Asimina triloba) trees exhibiting stunting and foliar mosaic, chlorosis, or distortions were observed in New York. In 2021, leaf samples from two symptomatic trees and a sapling, as well as two asymptomatic trees, were tested for the presence of viruses and viroids by high-throughput sequencing (HTS) using total RNA after ribosomal RNA depletion. HTS sequence information revealed tobacco ringspot virus (TRSV) and tomato ringspot virus (ToRSV) in symptomatic but not in asymptomatic leaves. HTS reads and de novo-assembled contigs covering the genomes of both viruses were obtained, with a higher average read depth for RNA2 than RNA1. The occurrence of TRSV and ToRSV was confirmed in the original leaf samples used for HTS and 12 additional trees and saplings from New York and Maryland in 2022 by RT-PCR combined with Sanger sequencing, and DAS-ELISA. Single infections by TRSV in 11 of 14 trees and dual infections by TRSV and ToRSV in 3 of 14 trees were identified. The nucleotide sequence identity of partial gene fragments of TRSV and ToRSV was high among pawpaw isolates (94.9–100% and 91.8–100%, respectively) and between pawpaw isolates and isolates from other horticultural crops (93.6–100% and 71.3–99.3%, respectively). This study is the first to determine the virome of pawpaw.